Functional Interaction Between Caveolin 1 and LRRC8-Mediated Volume-Regulated Anion Channel - Rezola, Mikel; Castellanos, Aida; Gasull, Xavier; Comes, Núria (Frontiers in Physiology, 2021)
Volume-regulated anion channel (VRAC), constituted by LRRC8 heteromers, is crucial for volume homeostasis in vertebrate cells. This widely expressed channel has been associated with membrane potential modulation, proliferation, migration, apoptosis and glutamate release. VRAC is activated by cell swelling and by low cytoplasmic ionic strength or intracellular GTP-γS in isotonic conditions. Despite the substantial number of studies that characterized the biophysical properties of VRAC, its mechanism of activation remains a mystery. Different evidence suggests a possible effect of caveolins in modulating VRAC activity: 1. Cav1-deficient cells display insignificant swelling-induced Cl- currents mediated by VRAC, which can be restored by Cav1 expression. 2. Cav3 knockout mice display reduced VRAC currents. 3. Interaction between LRRC8A, the essential subunit for VRAC, and Cav3 has been found in transfected HEK-293 cells. Here we demonstrate a physical interaction between endogenous LRRC8A and Cav1 proteins, that it is enhanced by hypotonic stimulation, suggesting that this will increase the availability of the channel to Cav1. In addition, LRRC8A targets plasma membrane regions outside caveolae of HEK-293 cells where it would associate with non-caveolar Cav1. We propose that a rise in cell membrane tension by hypotonicity would flatten caveolae, as described previously, increasing the amount of Cav1 outside of caveolar structures interacting with VRAC. Besides, expression of Cav1 in HEK Cav1- cells increases VRAC current density without changing the main biophysical properties of the channel. The present study provides further evidence on the relevance of Cav1 on the activation of endothelial VRAC through a functional molecular interaction.